Kondisi Sanitasi Dasar Masyarakat Desa Pingaran Ulu Kecamatan Astambul Kabupaten Banjar Tahun 2014 - Tien Zubaidah; Arifin Arifin (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2014)
Abstract: Basic Sanitary Conditions At Pingaran Ulu Village Community Subdistrict Astambul, Banjar District Year 2014. Basic sanitation monitoring efforts are directed towards environmental factors that can constitute the chain of transmission of the disease, which include water supply, wastewater disposal, disposal of human waste / family latrines and waste management. Basic sanitary conditions must be able to meet the physical needs, the reality is difficult to be met and most of the population because of the level of education, social science and economics. To know the basic sanitary conditions descriptive survey research is to use the checklist and guided interview questionnaire to 249 households. The purpose of the study to determine the means of water supply, disposal of excreta and wastewater, waste management, and the factors that influence those described in the form of frequency distribution tables and narrative. The result showed a percentage overview of basic sanitation Pingaran Ulu villagers who do not qualify ie water supply as much as 80% comes from the river water, excreta disposal as much as 89% of people throw in the river, wastewater by 75% without management, waste management how to burn garbage as much as 56%. This is due to the level of education, low socioeconomic majority. It is expected the public to pay attention to the quality of basic sanitation, income generation so that people can repair and build basic sanitation facilities and healthy home by way of mutual assistance / social gathering under the guidance of the relevant service agencies. For the Banjar District Health Office and Health Center Astambul should be able to spearhead the development of basic sanitation and a healthy home.Keywords: basic sanitation; village Ulu Pingaran